Characteristics and influencing factors of red blood cell distribution width in peritoneal dialysis patients of different ages - ZHANG Qi; CAO Xue-ying; ZHOU Jian-hui; HUANG Jing; CAI Guang-yan; CHEN Xiang-mei (Linchuang shenzangbing zazhi)
Objective Red blood cell distribution width(RDW) has been proven to be an independent predictor of mortality in chronic hemodialysis patients.This study aimed to explore the characteristics and influencing factors of the RDW in peritoneal dialysis patients.Methods The study enrolled 103 uremic patients on CAPD.Patients were categorized into three groups according to their age(patients in group 1 were under the age of 40;group 2:aged between 40 and 59;group 3:aged above60).The differences of clinical parameters among three groups were analyzed,and the influence of age and gender on RDW was analyze by multiple linear regression.Results The proportion of subjects with RDW value above 14.6%in female gender was higher than in male gender on the baseline,one month and three months after peritoneal dialysis(13.5%,15.4%,17.3%vs.9.8%,7.8%,13.7%).The baseline RDW of the group 3 was significantly higher than that of the other groups.Age was positively associated with the RDW on the baseline and one month after dialysis.The multiple linear regression analysis revealed that after the corresponding BMI adjusted,the baseline RDW was associated with female gender(β= 0.025,P<0.001,95%CI:0.001- 0.953) and increasing age(β= 0.025,P<0.001,95%CI 0.010- 0.040),and RDW at one month after dialysis was related to the increasing age(β= 0.015,P<0.05,95%CI 0.001- 0.029).After making further adjustments of hemoglobin,albumin and eGFR(or residual renal GFR),increasing age remained associated with RDW on the baseline(β= 0.027,P<0.001,95%CI 0.011- 0.042) and one month after dialysis(β=0.017,P<0.05,95%CI 0.003-0.031).Conclusions The influencing factors of RDW,and its mechanism of predicting dialysis patients’ prognosis are not clear.This study found that the elevated RDW was associated with age,which provides a new insight to improve the prognosis of the elderly patients in peritoneal dialysis.